Influence of the ground effect on airdrop mission performance analysis. (12th February 2018) - Mao, Yuhao; Dong, Wenhan; Zhu, Jiahai; Liu, Ri; Chang, Jinyong
Aimed at determining the ground effect's influence on the process of ultralow-altitude airdrop, this article studies the corresponding changes in aerodynamic characteristics caused by the ground effect. Through analyzing the longitudinal long- and short-period modes and the lateral mode, this work evaluates the impact that the ground effect has on the level-off and the traction stages during an airdrop mission, with reference to corresponding flight quality standards. Accordingly, these findings provide a reference for the design of flight control regarding airdrop capabilities and support a theory for corresponding ground experiments.